A Structural Equation Model for Sustainable Supply Chain Management in the Food Industry - Theofilos D. Mastos; Katerina Gotzamani; Petros Ieromonachou; George Tsiotras (Foods)
This paper presents a model designed to measure and investigate the relationships between critical factors, practices, and performance of sustainable supply chain management (SSCM) in the food industry. A survey of 423 firms in the Greek food industry was conducted to meet these objectives. The data were analyzed using exploratory factor analysis, followed by confirmatory factor analysis and structural equation modeling, to explore the relationships between the model’s constructs. The results indicate that “firm-level critical sustainability factors” and “supply chain critical sustainability factors” significantly enhance “supply chain collaboration” and “supply chain strategic orientation”. Additionally, “supply chain strategic orientation” positively influences “social performance” and “environmental performance”, while “supply chain collaboration” positively affects “economic performance” and “environmental performance”. Furthermore, “social performance” is found to have a significant positive impact on “economic performance”. This study provides empirical evidence that helps managers understand the importance of the relationships among SSCM critical factors, SSCM practices, and SSCM performance, and enables them to allocate resources effectively and design SSCM strategies. Finally, the developed constructs offer a measurement tool useful for both practitioners implementing SSCM in their firms and researchers who wish to apply or test the proposed scales in other projects or use them as benchmarks.